(untitled) (Journal of Geography and Environmental Management, 2021)
The article presents the results of research on the long-term dynamics of wetlands in the Ile River delta. Degradation of the wetland environment in the Ile delta is currently an important environmental problem. Due to the decline in the water of the Ile River, droughts and anthropogenic activities in the region in the last century, especially in the last five decades, have led to the degradation of wetlands. The results of the study show that changes in wetlands cover the entire delta area, that is, a decrease in surface water and, therefore, the disappearance of wetlands and an increase in dry land. Given the fact that the delta of the Ile River occupies a large area, remote sensing methods, as well as the results of previous research in the region were widely used in the study. As research data, we used the results of earlier studies performed by the method of interpreting aerial photographs of the study area from 1958 to 1975. From 1985 to 2015 data from the Landsat satellite were used. In addition, a set of direct field work in the study area to determine the accuracy of the data obtained from space images was carried out. Looking at recent satellite images of the Ili river Delta, we can see that even the main part of the Delta is not naturally moistened in early spring, so the future ecological state of the current Delta will depend entirely on river water regulation.